EKSISTENSI ASURANSI ANGGOTA TUBUH DI INDONESIA DALAM SUDUT PANDANG HUKUM EKONOMI SYARIAH - Ihwan, Miftakhul; Subekhan, Muhammad; Prasetya, Muhammad Fikry; Baidhowi, Baidhowi (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
Insurance is an effort to reduce the risks that will be experienced one day, considering that these risks can happen to everyone and threaten their interests, starting from property, life, to members of the body. In fact, limb insurance has grown rapidly abroad and has been used by many artists, athletes, musicians, food and beverage critics, and so on. The presence of asurasni limbs in Indonesia has actually been widely used by several Indonesian artists. However, Indonesia does not yet have related laws and regulations, with this phenomenon how Islamic economic law reacts to it. Because of this, the purpose of this study is to formulate the problem of how the development of limb insurance and to find out how the presence of limb insurance in Indonesia is from the perspective of sharia economic law. This writing is a normative law writing that uses data collection techniques by means of library research, with descriptive analysis research specifications. The conclusion is that the presence of limb insurance is actually allowed in Islamic economic law, of course it must be in accordance with Islamic principles and not violate the rules therein.